An air transport marketing initiative: are frequent flyer programmes desirable from the point of view of consumer protection and competition law in Europe? - Storm, Susanne (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
Frequent flyer programmes are a recent marketing strategy introduced first in the US and later also in Europe in connection with deregulation and liberalization of the markets for air transport. They are very powerful instruments in the hands of airlines both to keep their customers loyal and to keep smaller competing airlines out of the market. The European Commission has not taken a stand about their desirability on the market. The paper looks at the programmes from the standpoint of competition law and consumer protection with the basic assumption that they are undesirable on the market. Some proposals for regulating the programmes are put forward in connection with the analyses.